Mild Cognitive Impairment, Dementia, and Affective Disorders in Essential Tremor: A Prospective Study. (24th June 2014) - Sinoff, Gary; Badarny, Samih
Background: It is now reported that non-motor features, cognitive and affective problems, are becoming a major factor in essential tremor (ET). The aim of this study was to investigate the prevalence of cognitive and affective dysfunction in ET and to prospectively follow-up changes in the subjects. Methods: Fifty-two persons over the age of 50 years were recruited from the Movement Disorder Clinic. The subjects underwent baseline neurological, cognitive, and mood assessments and repeat assessment 2 years later. Results: The mean age was 68 years, with an average age of ET onset of 55.8 years and with a mean disease duration of 11.7 years. At initial cognitive assessment using various instruments and the Clinical Dementia Rating Scale, 69.2% had mild cognitive impairment (MCI). There were disturbances in phonemic fluency, verbal memory, concentration, and semantic fluency; 25% suffered from anxiety and 17.6% from depression. During the 2 years there was an annual 8.4% conversion rate to dementia, with all convertors initially suffering from MCI. Another 25% converted from no initial cognitive impairment to MCI within 2 years. At follow-up the same percentage was still suffering from anxiety. Discussion: The study confirms our hypothesis that ET patients suffer from MCI and anxiety. Though a control group was not used, the conversion rates for patients without ET and with/without MCI are known. The uniqueness of this study is that at follow-up, those with ET and MCI had a similar conversion rate to dementia to those suffering from MCI only. Additionally, persons with ET and no initial cognitive impairment were found to be at greater risk for developing MCI than the normal population. Clinicians must increase their awareness of cognitive impairment and anxiety in persons with ET and begin immediate treatment when indicated.